Construct Validity and Reliability of the South Oaks Gambling Screen Among the Indonesian Population - Siste, Kristiana; Sinambela, Yenny Siti Yanti; Hanafi, Enjeline; Murtani, Belinda Julivia; Putri, Kassie Gracella; Damayanti, Reza; Ginting, Tribowo Tuahta; Joewana, Satya; Sen, Lee Thung (Journal of the Korean Academy of Child and Adolescent Psychiatry, 2025)
This study aimed to evaluate the validity and reliability of the Indonesian version of the South Oaks Gambling Screening (SOGS), the most widely used tool for screening gambling disorder (GD). A national cross-sectional study was conducted between April and July 2021 among an Indonesian community sample. A total of 5810 respondents participated (mean age=21.74±5.68 years; 76.8% were women). The methodology included forward translation, expert panel discussions, back translation, face validity testing, a pilot study, and an assessment of the SOGS's psychometric properties. Factor structure was examined using exploratory and confirmatory factor analysis, and reliability was assessed using Cronbach's alpha. Factor analysis revealed that the Indonesian version of the SOGS consisted of four domains and demonstrated satisfactory goodness of fit (χ =1270.72; df=166; p<0.001; RMSEA=0.048; CFI=0.99; TLI=0.99; SRMR=0.031). The SOGS also showed good internal consistency (Cronbach's alpha=0.879). Findings indicated that 2.05% of the sample met the criteria for gambling addiction. A significant association was observed between GD and age (p<0.001), sex (p<0.001), educational level (p<0.05), employment status (p<0.001), and types of gambling (p<0.001). The Indonesian version of SOGS is a valid and reliable instrument for assessing GD in the Indonesian population.